2019
DOI: 10.1111/ases.12759
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of bowel perfusion assessment during laparoscopic colorectal resection using laser speckle contrast imaging: A matched case–control study

Abstract: IntroductionDisadvantages of bowel perfusion assessment with indocyanine green fluorescence angiography include the need for a fluorophore and the subjective nature of the assessment. This study was performed to evaluate the clinical efficacy of bowel perfusion assessment using laser speckle contrast imaging (LSCI) during laparoscopic colorectal surgery.MethodsThe study population comprised the first 27 consecutive patients who underwent laparoscopic left‐sided colorectal resection with intraoperative perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Postoperative wound infection was reported in 8 studies (20,31,32,34,36,40,42,45) (2 RCTs, 6 PSM studies), ICG did not reduce the risk of postoperative wound infection, and there was no significant heterogeneity between studies (OR, 0.76; 95% CI, 0.44, 1.32; P = 0.33; I 2 = 0%) (Figure 6B). Both RCTs (20, 40) (OR, 0.52; 95% CI, 0.15, 1.89; P = 0.32; I 2 = 16%) (Table 3) and PSM studies (31,32,34,36,42,45) (OR, 0.84; 95% CI, 0.45, 1.57; P = 0.58; I 2 = 0%) (Table 3) showed that ICG does not reduce the incidence of postoperative wound infection.…”
Section: Wound Infectionmentioning
confidence: 98%
See 4 more Smart Citations
“…Postoperative wound infection was reported in 8 studies (20,31,32,34,36,40,42,45) (2 RCTs, 6 PSM studies), ICG did not reduce the risk of postoperative wound infection, and there was no significant heterogeneity between studies (OR, 0.76; 95% CI, 0.44, 1.32; P = 0.33; I 2 = 0%) (Figure 6B). Both RCTs (20, 40) (OR, 0.52; 95% CI, 0.15, 1.89; P = 0.32; I 2 = 16%) (Table 3) and PSM studies (31,32,34,36,42,45) (OR, 0.84; 95% CI, 0.45, 1.57; P = 0.58; I 2 = 0%) (Table 3) showed that ICG does not reduce the incidence of postoperative wound infection.…”
Section: Wound Infectionmentioning
confidence: 98%
“…Postoperative wound infection was reported in 8 studies (20,31,32,34,36,40,42,45) (2 RCTs, 6 PSM studies), ICG did not reduce the risk of postoperative wound infection, and there was no significant heterogeneity between studies (OR, 0.76; 95% CI, 0.44, 1.32; P = 0.33; I 2 = 0%) (Figure 6B). Both RCTs (20, 40) (OR, 0.52; 95% CI, 0.15, 1.89; P = 0.32; I 2 = 16%) (Table 3) and PSM studies (31,32,34,36,42,45) (OR, 0.84; 95% CI, 0.45, 1.57; P = 0.58; I 2 = 0%) (Table 3) showed that ICG does not reduce the incidence of postoperative wound infection. Subgroup analysis showed that ICG did not reduce the incidence of postoperative wound infection during colorectal surgery (20,36,40,42) (OR, 0.60; 95% CI, 0.32, 1.15; P = 0.13; I 2 = 0%) (Table 3) or low anterior resection (31,32,34,45) (OR, 1.38; 95% CI, 0.49, 3.89; P = 0.55; I 2 = 0%) (Table 3).…”
Section: Wound Infectionmentioning
confidence: 98%
See 3 more Smart Citations